2019
DOI: 10.2147/cmar.s186829
|View full text |Cite
|
Sign up to set email alerts
|

<p>USP13 serves as a tumor suppressor via the PTEN/AKT pathway in oral squamous cell carcinoma</p>

Abstract: Background: Recent studies have shown that USP13 a deubiquitinase, serves as an important regulator of tumorigenesis. However, the biological role of USP13 in oral squamous cell carcinoma (OSCC) remains enigmatic.Materials and methods: We examined USP13 expression in OSCC and adjacent normal tissues by immunohistochemical staining. The biological functions of USP13 in OSCC cells and the possible underlying mechanisms were investigated.Results: In this study, we showed that USP13 expression was frequently reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…Therefore, research on deubiquitinating enzymes has always attracted much attention to the pharmaceutical industry. Research in recent decades has shown that deubiquitinating enzymes can regulate multiple signaling pathways [33][34][35][36], suggesting to researchers the development of new medicines based on the pathogenesis of different diseases that can target deubiquitinating enzymes. For example, the development of deubiquitinating enzyme inhibitors [185], especially selective inhibitors, may have a good therapeutic effect [186,187].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, research on deubiquitinating enzymes has always attracted much attention to the pharmaceutical industry. Research in recent decades has shown that deubiquitinating enzymes can regulate multiple signaling pathways [33][34][35][36], suggesting to researchers the development of new medicines based on the pathogenesis of different diseases that can target deubiquitinating enzymes. For example, the development of deubiquitinating enzyme inhibitors [185], especially selective inhibitors, may have a good therapeutic effect [186,187].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, disease treatment strategies with DUBs as molecular targets have a broad development value and promising clinical application prospects [32]. Many studies have shown DUBs involvement in the regulation of Wnt/β-catenin signaling, TGF-β (transforming growth factor-β), Akt (Protein Kinase B), NF-κB (nuclear factor kappa-lightchain-enhancer of activated B cells) and other cancer-related pathways [33][34][35][36].…”
Section: Dubs In Diseasesmentioning
confidence: 99%
“…The data in the literature regarding the role of USP13 in carcinogenesis is controversial. Some studies propose that USP13 favors tumor progression and plays an oncogenic role in glioma [ 30 ], melanoma [ 31 ], ovarian cancer [ 32 ] and lung cancer [ 33 ] while others claim that it functions as a tumor suppressor in oral squamous cell carcinoma [ 34 ], breast cancer [ 15 ] and bladder cancer [ 35 ]. Collectively, these data suggest a context-dependent role for USP13 in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…USP13 also acts as a tumor suppressor through its regulation of the phosphatase and tensin homolog deleted on chromosome 10 (PTEN)/AKT pathway in oral squamous cell carcinoma. Overexpression of USP13 induces PTEN expression and represses the activation of AKT, glucose transporter-1, and hexokinase-2, leading to growth inhibition [84]. In an RNAi screen, USP11 was identified as a promyelocytic leukemia (PML) regulator to deubiquitinate and stabilize PML, counteracting the functions of PML.…”
Section: Dubs and Tumor Suppressors/oncogenesmentioning
confidence: 99%